How registry data are used to inform activities for stroke care quality improvement across 55 countries: A cross-sectional survey of Registry of Stroke Care Quality (RES-Q) hospitals - Fasugba, Oyebola; Sedani, Rupal; Mikulik, Robert; Dale, Simeon; Vařecha, Miroslav; Coughlan, Kelly; McElduff, Benjamin; McInnes, Elizabeth; Hladíková, Sabina; Cadilhac, Dominique A; Middleton, Sandy (European journal of neurology, 2024)
BACKGROUND AND PURPOSE: The Registry of Stroke Care Quality (RES-Q) is a worldwide quality improvement data platform that captures performance and quality measures, enabling standardized comparisons of hospital care. The aim of this study was to determine if, and how, RES-Q data are used to influence stroke quality improvement and identify the support and educational needs of clinicians using RES-Q data to improve stroke care. METHODS: A cross-sectional self-administered online survey was administered (October 2021-February 2022). Participants were RES-Q hospital local coordinators responsible for stroke data collection. Descriptive statistics are presented. RESULTS: Surveys were sent to 1463 hospitals in 74 countries; responses were received from 358 hospitals in 55 countries (response rate 25%). RES-Q data were used "always" or "often" to: develop quality improvement initiatives (n = 213, 60%); track stroke care quality over time (n = 207, 58%); improve local practice (n = 191, 53%); and benchmark against evidence-based policies, procedures and/or guidelines to identify practice gaps (n = 179, 50%). Formal training in the use of RES-Q tools and data were the most frequent support needs identified by respondents (n = 165, 46%). Over half "strongly agreed" or "agreed" that to support clinical practice change, education is needed on: (i) using data to identify evidence-practice gaps (n = 259, 72%) and change clinical practice (n = 263, 74%), and (ii) quality improvement science and methods (n = 255, 71%). CONCLUSION: RES-Q data are used for monitoring stroke care performance. However, to facilitate their optimal use, effective quality improvement methods are needed. Educating staff in quality improvement science may develop competency and improve use of data in practice.
Keywords: Hospitals; clinical quality registry; cévní mozková příhoda; quality improvement; Quality of Health Care; stroke; Humans; kvalita zdravotní péče; rutinně sbírané zdravotní údaje; průřezové studie; Routinely Collected Health Data; Quality Improvement; Cross-Sectional Studies; Registries; nemocnice; data; registrace; Stroke; zlepšení kvality; lidé